Oxidative stability of soybean oil added to Lentinus edodes and Agaricus blazei mushrooms extracts in an accelerated storage test - da Silva, Ana Carolina [UNESP]; Jorge, Neuza [UNESP] (Emerald, 2012)
Purpose: The purpose of this paper is to evaluate the oxidative stability of soybean oil added by Lentinus edodes and Agaricus blezei extracts in accelerated storage test. Design/methodology/approach: The following treatments were subjected to accelerated storage test in an oven at 60°C for 15 days: Control (soybean oil without antioxidants), TBHQ (soybean oil + 100 mg/kg of TBHQ), BHT (soybean oil + 100 mg/kg of BHT), L. edodes (soybean oil + 3,500 mg/kg of L. edodes extract) and A. blazei (soybean oil + 3,500 mg/kg of A. blazei extract). The samples were taken every three days and analyzed for peroxide values and conjugated dienes. Findings: At the end of 15 days, the treatments TBHQ, A. blazei, L. edodes, Control and BHT showed 6.47, 8.81, 41.53, 71.28 and 78.40 meq/kg, respectively, for peroxide values and 0.37, 0.40, 0.67, 1.07 and 1.00 per cent, respectively, for conjugated dienes. Originality/value: The research indicates that mushrooms may be a promising source of natural antioxidants. Therefore, natural extracts of mushrooms can be applied to vegetable oils as a way to reduce the degradation caused by lipid oxidation. © Emerald Group Publishing Limited.
Keywords: Conjugated dienes; Fungi; Mushrooms; Oils; Oxidation; Peroxide values; Soya; Agaricus; Agaricus blazei; Basidiomycota; Glycine max; Lentinula edodes